Índices de adiposidade e doença hepática gordurosa não alcoólica: estudo da associação com marcadores de doença renal. - Alexandra Dias Moreira (2017)
Evidence suggests an association between obesity, non-alcoholic fatty liver disease (NAFLD) and renal disease, regardless of other risk factors, such as hypertension, diabetes, dyslipidemia. Objective: To test the association between anthropometric indices, non-alcoholic fatty liver disease and CKD markers. Methods: Cross-sectional study, with 14636 participants in the study of anthropometric measures and 10114 in the study of NAFLD, after exclusion of individuals reporting excessive alcohol consumption or history of cirrhosis and/or hepatitis. The participants, aged 35 to 74 years old, were from the baseline of the ELSA - Brazil. The response variables were the glomerular filtration rate (GFR) estimated by the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation, and albuminuria, estimated by the albumin-creatinine ratio, categorized as yes (30 mg / g) and no (<30mg / g). The main exposures evaluated were: obesity (BMI) body mass index 30 kg / m2), altered waist circumference (WC) (102 cm in men and 88 cm in women), altered waist to hip ratio (WHR) ( 94 cm in men and 80 cm in women), altered waist to height ratio (WheiR) (0.5) and presence of NAFLD defined by hepatic ultrasonography. In order to estimate the association between the main exposures and glomerular filtration rate and albuminuria, linear and logistic regression analyzes were performed, respectively, with univariate and multivariate models adjusted for sociodemographic, behavioral variables, metabolic syndrome or its componentes, history of kidney disease, and in the study of non-alcoholic fatty liver disease, also by liver enzymes variables. A level of statistical significance of 5% was considered. Results: After adjustment, individuals with obesity, altered WC, altered WHR and altered WheiR presented a greater chance of albuminuria when compared to individuals with normal values for these measures (OR: 1.25 95% CI 1.05 -1.48 OR: 1.41 95%CI 1.19-1.67 OR: 1.42 95% CI 1.13-1.77 OR: 1.30 95% CI 1.01-1.68, respectively). Individuals with severe NAFLD had a double chance of albuminuria when compared to those without liver disease (OR: 2,07 95%CI 1,37 3,15). In addition, an inverse association between obesity, altered WC and GFR was found in the adjusted linear regression analyzes (: -0.12; 95% CI -0.18 - -0.07 and -0.03 95% CI -0.05 - -0.01, respectively) and NAFLD was not associated to GFR after adjustment for confounders. Conclusion: These results confirm that obesity and NAFLD may be potential risk factors for the kidney disease.